Prevention of wounds in patients with diabetes mellitus in the nursing process: A literature review - Tata, Jernilai Since; Gurning, Maylar; Mannopposem, Inggerid A (Science Center Group, 2024)
Background: Diabetes mellitus is a chronic metabolic disorder that increases the risk of complications, including diabetic foot wounds that may lead to infection, disability, and reduced quality of life. Preventive strategies are therefore essential within the nursing process to minimize the occurrence of diabetic foot complications. Objective: This study aimed to synthesize evidence related to prevention of wounds in patients with diabetes mellitus within the framework of the nursing process. Methods: This study employed a literature review design following PRISMA guidelines. Articles were retrieved from Google Scholar using keywords related to diabetes mellitus, diabetic foot wounds, prevention, and foot care knowledge. Inclusion criteria consisted of research articles published between 2019 and 2024 that focused on preventive strategies for diabetic foot wounds. Ten eligible studies were included after screening and full-text evaluation. Data extraction included study characteristics, research objectives, design, and key findings. Narrative synthesis was used to analyze the results. Results: The review identified that patient knowledge, preventive behaviors, family support, and nursing interventions are important determinants of diabetic wound prevention. Studies consistently reported significant relationships between patient knowledge and preventive foot care practices. Educational interventions, regular foot examination, proper footwear use, and family involvement were shown to strengthen preventive behaviors. The nursing process also provides a structured framework that supports early risk assessment, patient education, and monitoring of preventive practices. Conclusion: Prevention of diabetic wounds requires integrated nursing interventions that emphasize patient education, family participation, and systematic foot care assessment. Strengthening preventive strategies within the nursing process may reduce the risk of diabetic foot complications and improve patient outcomes.